Análise da aplicação do polímero de fécula de mandioca como floculante auxiliar do cloreto férrico no tratamento de água por sedimentação - Silva, Léon Edson Ferreira (2019)
The present work has as main objective to evaluate the use of the cassava starch polymer (PFM) as an auxiliary flocculent of the ferric chloride (CF) to reduce water turbidity by means of coagulation / flocculation treatment followed by sedimentation. The turbid water samples for the study were collected in a pond located in the city of Santa Maria in the state of Rio Grande do Norte. For the analyzes of the behavior of the cassava starch polymer as an auxiliary of the ferric chloride in the treatment of water by sedimentation, a floatateste constructed on bench scale was used. All the tests were performed in duplicate, always respecting the formulation of the samples made by the system with the starch-chloride mixture (PFM + CF), altering only in each system used the percentage of starch concentration and ferric chloride, following the values of 0%, 25%, 50% and 100% of each flocculant at the sedimentation time of one hour for each of the mounted systems. For each concentration system mentioned, a coagulation/flocculation/sedimentation experiment was performed, in which turbidity, conductivity and pH of the samples were measured before and after the experiment, in order to determine the efficiency of the process. For the proposed systems cassava starch did not play a satisfactory role as a flocculating aid for ferric chloride. The system containing only ferric chloride had the highest percentage of turbidity removal (84.63%) while the system only had the lowest cassava starch (19.26%). The influence of the starch in the electrical conductivity of the treated water can not be defined, presenting great variation, while in the pH, it minimized the fall of its value caused by the addition of the ferric chloride.